Integration of Islamic Economics with Modern Financial Systems: Challenges and Opportunities for Sharia-Compliant Growth - Mira Chairani; Nurhalimah Lubis; Munawaroh (INTERNATIONAL, Journal of Sharia Business Management, 2024)
This article discusses the integration of the economy with the modern financial system and facing its opportunities and challenges. With the intention of informing the public about the application of Islamic economics in the financial system and its benefits for the country and society. This article is conducted with a literature review whose sources are obtained from books, articles, websites, and other supporting sources. The application of Islamic economic principles in a country can increase the country's economic growth which in practice will bring benefits to the people as a whole. The importance of implementing Islamic economics in the modern financial system so that its innovations can also improve society in the application and use of the modern Islamic financial system.